PERTUMBUHAN DAN REPRODUKSI IKAN KEMBUNG LELAKI (Rastrelliger kanagurta Cuvier 1817) YANG DIDARATKAN DI PPN PALABUHAN RATU - Muhammad Arif Nasution; Mohammad Mukhlis Kamal; Kiagus Abdul Azis (Universitas Teuku Umar, 2015)
The aim of this study to predict and explaine growth and reproduction aspect of indian mackerel (Rastrelliger kanagurta) . The study conducted from March to April 2014, with sample and data collection in the field covering total length and weight of the body, whereas in the laboratory such as gonad weight, volume and diameter of the egg. The results showed regression equation of length-weight relationship Rastrelliger kanagurta is W=2.98E-06L3.2351474. Growth model Lt = 368.8 [1-exp-0.48(t+0.17)] were L∞ = 368.8 mm and K = 0.48/month with first mature at lenght 170 mm. the number of eggs in the Rastrelliger kanagurta ovary between 42.606 – 63.043, Eggs diameter ranged from 0.28 to 0.56 mm. Growth pattern of Rastrelliger kanagurta is positif allometrik, take 48 months to reach maximum length.